ANALISIS PENERAPAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR SISWA X TKR3 SMK DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI PADA POKOK BAHASAN MATRIKS TAHUN PELAJARAN 2021/2022 - Susanti, Nawal Ika (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
This study aims to find out and analyze the application of the scramble learning model to student learning outcomes on the subject of the matrix. The sample used in this study was students of class X TKR3 SMK Darussalam, totaling 40 students. Collecting data in this study using observation and test methods. The test instrument was tested for validity using Pearson's correlation, reliability test using Crobach Alpha. In addition, a test of the difficulty level of the questions was also carried out. Data analysis in this study used data analysis of the Paired Sample T-Test. The results of testing the research hypothesis showed that there was a difference in the mean before and after the scramble learning model was applied to the learning outcomes of the subject matter matrix of class X TKR3 SMK Darussalam. The results of the study also show that the level of the mathematics learning outcomes category of students who study using the Scramble Method on the matrix subject matter of class X TKR3 SMK Darussalam Blokagung Tegalsari Banyuwangi is in the high category.